Gender and action films : road warriors, bombshells and atomic blondes - Gerrard, Steven; Middlemost, Renée (Emerald studies in popular culture and gender., 2022)
The noughties witnessed rapid change in Action Cinema, carrying with it the new action stars of the previous decade, and the boundary blurring experimentation of films such as The Matrix, that incorporated not only action but science fiction. The now dominant Marvel Cinematic Universe (MCU) debuted, and the Young Adult fictional worlds of Harry Potter and The Hunger Games further developed the scope of the action sequences. Despite this context, the action genre had still not engaged fully with contemporary social issues. Focusing on a less acknowledged period in Action Cinema history, Gender and Action Films: Road Warriors, Bombshells and Atomic Blondes examines specific action stars such as Michelle Rodriguez, Zhang Ziyi, and Pam Grier to analyse how female stars encounter the male gaze. Split into four parts - 'Star Bodies', 'Transmedia Action', 'Intergenerational Action' and 'Politics and Race', chapter authors prioritise female led action movies and champion a more meaningful interaction and representation between the action genre and contemporary issues of race, sexuality, and gender. Offering novel interpretations of depictions of gender within action movies, this edited collection demonstrates gender portrayal can be developed to incorporate meaningful representation in the wake of the movements such as #Oscarssowhite or #MeToo that have confronted Hollywood. The collection is a must-have for academics, students and lovers of film and media and those interested in gender studies.